Simulation of Friction Stir Spot Welding of Copper and Aluminium During Plunging Phase - Shobri, N.N.S.M. (IOP Publishing Ltd, 2021)
Simulation is limited and remains briefly addressed in the literature of friction stir spot welding (FSSW) process in joining dissimilar copper and aluminium. Thus, this study simulated the FSSW process of copper and aluminium to investigate the peak temperature during the plunging phase produced by all possible combinations of levels for tool rotational speed, plunge rate, and plunge depth according to the full factorial design. The modeling was established by Coupled Eulerian-Lagrangian (CEL) model and 'dynamic, temperature-displacement, explicit' analysis. The highest peak temperature of 994.4 oC was produced by 2400 rpm rotational speed, 100 mm/min plunge rate, and 1.6 mm plunge depth. The combination was suggested to be the optimum welding parameters in joining copper to aluminium as sufficient heat input was essential to soften the area around the welding tool and adequately plasticize the material. Three sets of confirmation tests presented consistent responses with a mean peak temperature of 994.4 oC, which validated that the response produced by the suggested optimum welding parameters was reliable. The statistical result reported that the variability in the factors could explain 84.12 of the variability in the response. However, only the rotational speed and plunge depth were statistically significant. The residual plots showed that the regression line model was valid. Â© 2021 Institute of Physics Publishing. All rights reserved.